3D‐printed holders for in meso in situ fixed‐target serial X‐ray crystallography. Issue 3 (23rd April 2020) - Huang, Chia-Ying; Meier, Nathalie; Caffrey, Martin; Wang, Meitian; Olieric, Vincent
Abstract : The design and assembly of two 3D‐printed holders for high‐throughput in meso in situ fixed‐target crystallographic data collection are described. Abstract : The in meso in situ serial X‐ray crystallography method was developed to ease the handling of small fragile crystals of membrane proteins and for rapid data collection on hundreds of microcrystals directly in the growth medium without the need for crystal harvesting. To facilitate mounting of these in situ samples on a goniometer at cryogenic or at room temperatures, two new 3D‐printed holders have been developed. They provide for cubic and sponge phase sample stability in the X‐ray beam and are compatible with sample‐changing robots. The holders can accommodate a variety of window material types, as well as bespoke samples for diffraction screening and data collection at conventional macromolecular crystallography beamlines. They can be used for convenient post‐crystallization treatments such as ligand and heavy‐atom soaking. The design, assembly and application of the holders for in situ serial crystallography are described. Files for making the holders using a 3D printer are included as supporting information.